2014
DOI: 10.1364/ao.53.00h170
|View full text |Cite
|
Sign up to set email alerts
|

Emulated laser-acupuncture system

Abstract: A novel laser-acupuncture system was developed that can be used to implement the manipulation methods of traditional acupuncture, such as lifting and thrusting. A 780 nm laser diode with a maximum power of 90 mW was used as the light source. The focus point of the laser beam was adjustable by changing the position of the lens, facilitating the implementation of the lifting and thrusting methods of traditional Chinese medicine and achieving various stimulation depths at the acupuncture point. The images for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Chang et al developed a new laser acupuncture system that uses a semiconductor laser tube as the light source. The focus of the laser beam was adjusted by changing the position of the lens to mimic the effect of lifting and thrusting in traditional acupuncture [34]. Litscher et al through their research found that continuous 405 nm blue laser light stimulation significantly reduces the heart rate of Chinese adults applied on Neiguan [35].…”
Section: A Related Workmentioning
confidence: 99%
“…Chang et al developed a new laser acupuncture system that uses a semiconductor laser tube as the light source. The focus of the laser beam was adjusted by changing the position of the lens to mimic the effect of lifting and thrusting in traditional acupuncture [34]. Litscher et al through their research found that continuous 405 nm blue laser light stimulation significantly reduces the heart rate of Chinese adults applied on Neiguan [35].…”
Section: A Related Workmentioning
confidence: 99%
“…These physiological signals are used in the diagnosis of human body imbalances or diseases, drawing upon findings from modern medical science and TCM’s eight-principle differentiation, defense-qi nutrient differentiation, organ visceral differentiation, six-meridian differentiation, qi blood body fluid differentiation, and triple-warmer differentiation diagnostic approaches [29] . Wang et al [30] set up an auxiliary acupuncture system that analyzes the patient’s symptoms of illness and determines a series of combinations of acupoints with a therapeutic effect, allowing the acupuncturist to treat patients with different acupoint prescriptions. Medical imaging techniques provide valuable supplemental support for TCM practitioners in the diagnosis of transient ischemic attacks.…”
Section: Bridging East and West: Advancements In Acupuncture Diagnosi...mentioning
confidence: 99%
“…With lift and thrust operation, specific effects such as reinforcement and reduction might be achieved during the acupuncture process. In our previous work, laser acupuncture instruments with the lift-thrust function have been developed [ 7 , 8 ]. Furthermore, we also showed that laser acupuncture with lift-thrust operation enabled a more rapid, stable, and lasting temperature rise of the fingertip than that without the lift-thrust operation [ 9 ].…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work, a novel laser acupuncture instruments with the lift-thrust function have been developed [ 7 , 8 ]. Specifically, the lift-thrust function of laser acupuncture is implemented by moving the focused laser spot back and forth.…”
Section: Introductionmentioning
confidence: 99%